Russian political philosophy : anarchy, authority, autocracy / Evert van der Zweerde. - Zweerde, Evert van der (Edinburgh studies in comparative political theory & intellectual history., 2022)
A focus on political philosophy as it existed and exists in Russia despite periods of marginalisation and suppression, allows us to understand its specific character, importance and relevance, and to realise that, in trying to think philosophically, critically, and reflectively about the political reality that shapes them, Russian thinkers are not essentially different from philosophers elsewhere. Hence, many lessons that can be learned from this subject.